Frailty and medical financial hardship among older adults with cancer in the United States - Lao, Jiahui; Su, Mingzhu; Zhang, Jiajun; Liu, Li; Zhou, Shengyu; Yao, Nengliang (Frontiers in Oncology, 2023)
Background: Little is known about the association between frailty level and medical financial hardship among older adults with cancer. This study aims to describe the prevalence of frailty and to identify its association with medical financial hardship among older cancer survivors in the United States. Methods: The National Health Interview Survey (2019–2020) was used to identify older cancer survivors (n=3,919). Both 5-item (Fatigue, Resistance, Ambulation, Illnesses, and Low weight-for-height) FRAIL and 3-domain (Material, Psychological, and Behavioral) medical financial hardship were constructed based on the NHIS questionnaire. Multivariable logistic models were used to identify the frailty level associated with financial hardship and its intensity. Results: 1,583 (40.3%) older individuals with cancer were robust, 1,421 (35.9%) were pre-frail, and 915 (23.8%) were frail. Compared with robust cancer survivors in adjusted analyses, frail cancer survivors were more likely to report material domain (OR=3.19, 95%CI: 2.16-4.69; P <0.001), psychological domain (OR=1.47, 95%CI: 1.15-1.88; P <0.001), behavioral domain (ORs ranged from 2.19 to 2.90, all with P <0.050), and greater intensities of financial hardship. Conclusions: Both pre-frail and frailty statuses were common in the elderly cancer survivor population, and frail cancer survivors were vulnerable to 3-domain financial hardships as compared with those with robust. Ongoing attention to frailty highlights the healthy aging of older survivors, and efforts to targeted interventions should address geriatric vulnerabilities during cancer survivorship.